An integrated early care pathway for autism. (May 2022) - Green, Jonathan; Leadbitter, Kathy; Ainsworth, John; Bucci, Sandra
Summary: In this Viewpoint, we argue for the need to reconceptualise an integrated early-care provision for autistic children in the light of their enduring support needs and relevant new findings from developmental and intervention research. This model goes beyond short-term reactive care to outline an early proactive, evidenced, developmentally phased, and scalable programme of support for autistic children and their families from the earliest opportunity, with timely access to later step-up care when needed. We also integrate this model with emerging opportunities from data science and digital health technologies as a potential facilitator of such a pathway. Building on this work, we argue that the best current autism intervention evidence can be integrated with concepts and evidence gained in the management of other enduring health conditions to support an autistic child and their family through their early development. The aim is to improve those children's social communication abilities, expand their range and flexibility of interests, and mitigate any negative impacts of sensory difficulties and restricted, repetitive behaviours on the child and their family wellbeing. The pathway solutions described could also be adapted for older adolescents and adults and could be used within the health systems of different countries, including within low-income and middle-income contexts.